NUCLEAR ORIENTATION BELOW 1-MK - DEVELOPMENT AND APPLICATIONS - Bradley, D; White, J; Ashworth, C; Rikovska, J; Stone, N (Kluwer Academic Publishers, 1987)
The Oxford top-loading PrNi5 nuclear demagnetisation stage /1/ has been further developed to reach temperatures below 1 mK. The hyperfine field for71As in nickel has been measured by low temperature nuclear orientation as 14.61(36)T. Measurements on transitions in71Ge yield spin values 3/2 (1299 kev and 1139 kev) and 5/2 (1027 kev) and 5 E2/M1 mixing ratios are given. © 1987 J.C. Baltzer A.G., Scientific Publishing Company.